2013
DOI: 10.1136/heartasia-2013-010297
|View full text |Cite
|
Sign up to set email alerts
|

Femoral artery pseudoaneurysm as a complication of angioplasty. How can it be prevented?

Abstract: Femoral pseudoaneurysm is a common complication of repeated femoral puncture during cardiac catheterisation. We describe here the development of femoral pseudoaneurysms in a patient with Takayasu's arteritis, which healed in response to conservative treatment, and review the literature on the prevention and treatment of femoral pseudoaneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…Selten wird die digitale Subtraktionsangiografie (DSA), die neben der Diagnostik auch therapeutisch angewendet werden kann, gewählt. Eine DSA sollte nur in Ausnahmefällen eingesetzt werden, da hier die Gefahr eines weiteren Pseudoaneurysmas besteht [14]. Sie sollte nur in Interventionsbereitschaft zur Sanierung des Aneurysmas eingesetzt werden.…”
Section: Resultsunclassified
“…Selten wird die digitale Subtraktionsangiografie (DSA), die neben der Diagnostik auch therapeutisch angewendet werden kann, gewählt. Eine DSA sollte nur in Ausnahmefällen eingesetzt werden, da hier die Gefahr eines weiteren Pseudoaneurysmas besteht [14]. Sie sollte nur in Interventionsbereitschaft zur Sanierung des Aneurysmas eingesetzt werden.…”
Section: Resultsunclassified
“…[ 8 9 10 11 12 13 14 15 16 17 ] Pseudoaneurysm formation is typically secondary to iatrogenic injury to the vessel wall, which may occur more frequently in patients with vasculopathy. [ 18 ] Commonly used strategies to avoid femoral artery pseudoaneurysm include locating the neck of the femur to avoid profunda femoris puncture, the Seldinger puncturing technique, and adequate compression after sheath removal, such measures mitigate but do not obviate risk. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…When a hematoma accompanying tenderness while the vibration thrill of the femoral artery is felt or bruit is auscultated, further evaluations of pseudoaneurysm should be performed. [3] Color Doppler ultrasonography, the most common test, is used to confirm the presence of a communicating tract and pseudoaneurysm number and size. When a pseudoaneurysm is large, its location and size can be identified more precisely using contrast-enhanced CT or MRI.…”
Section: Discussionmentioning
confidence: 99%
“…[2] In particular, pseudoaneurysm frequently occurs at the puncture site below the head of the femur due to insufficient bone support resulting in angiopressure after catheter removal. [3] However, to our knowledge, only a few studies have reported local complications after cerebral angiography. Here we describe 2 cases of femoral artery pseudoaneurysm after cerebral angiography and a review of the relevant literature.…”
Section: Introductionmentioning
confidence: 99%